Bilateral kissing molars involving a dentigerous cyst: report of a case and discussion of terminology. (11th September 2014) - Nedjat‐Shokouhi, B.; Webb, R.M.
Abstract: Kissing molars are a rarely reported form of impacted teeth, in which two molars have contacting occlusal surfaces in a single follicular space, with roots pointing in opposite directions. In this article we present a case of bilateral kissing molars with one side involving a dentigerous cyst; there have been no such previously reported cases in the literature. In this article we also discuss some of the aetiological and clinical implications of kissing molars, as well as the controversy over the precise use of this term. To enable simpler and more accurate reporting of such cases, we propose the use of the terms 'true' and 'pseudo‐' kissing molars, whereby the former should be used to classify impacted molars as originally described, and the latter to be used for any case of a similar nature but which does not completely fulfil these criteria.